Peningkatan Pengetahuan Budaya dan Pemahaman Siswa Melalui One Day Trip Luar Negeri di Singapura - Hulu, Fasaaro; Samad, Samad; Laia, Fanolo; Mokorimban, Hesty Bertha D. (PUAN INDONESIA, 2024)
This student mentoring activity was carried out for one day in Singapore and aimed to enrich knowledge, cultural understanding and educational and technological development in Singapore through, “One Day Trip Singapore activity”. Students are given basic English assistance and understanding of cultural knowledge while in Singapore. The result of this mentoring are the students could increase their confidence in speaking English with the tourists and Singaporean citizens, Participants can comply with the culture of queuing in public places, Participants understand the use of escalators for users who walk fast and elderly users, Participants understand the differences in currency and value, as they spent when they make transactions at the cashier, Participants understand the culture of fast walking and are motivated to participate when walking together in public places, participants maintain cleanliness while in public places and in all places in Singapore, along with understanding the use of restrooms and participants understand the lion statue The fish tail in Singapore is an icon of the country of Singapore which is based on the native Malay people who work as fishermen.